Severe hypothermia, bradycardia and cardiac arrest in association with risperidone. Issue 5 (20th May 2020) - Sharma, Nishant; Bhat, Sangeeta; Ravi, Divya; Ochieng, Pius
Abstract : Antipsychotic medications, including risperidone, are widely used in the treatment of psychiatric disorders, including schizophrenia. While hyperthermia is an establish adverse effect of these medications, less is known about the rare occurrence of hypothermia. We present two patients who developed hypothermia, bradycardia and cardiac arrest in association with risperidone. We briefly review previously similarly reported cases.